1992
DOI: 10.1002/bimj.4710340713
|View full text |Cite
|
Sign up to set email alerts
|

The S‐Distribution A Tool for Approximation and Classification of Univariate, Unimodal Probability Distributions

Abstract: SummaryIn many statistical applications a data set needs to be evaluated but there is no solid information about which probability distribution might be most appropriate. Typical solutions to this problems are: to make assumptions that facilitate mathematical treatment; to use a family of distribution functions that contains all relevant distributions as special cases; or, to employ nonparametric methods. All three solutions have disadvantages since assumptions are usually difficult to justify, families of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 16 publications
2
53
0
Order By: Relevance
“…Recognizing that cumulative distribution functions always grow monotonically from 0 to 1 and very much resemble growth functions, Voit proposed a single S-system equation as a good approximation of cumulative distribution functions, calling it the S-distribution [731]. It turned out that this S-distribution has interesting features.…”
Section: Recastingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recognizing that cumulative distribution functions always grow monotonically from 0 to 1 and very much resemble growth functions, Voit proposed a single S-system equation as a good approximation of cumulative distribution functions, calling it the S-distribution [731]. It turned out that this S-distribution has interesting features.…”
Section: Recastingmentioning
confidence: 99%
“…For instance, the initial value is directly related to the median of the distribution, the rate constant, which must be the same for both terms in the S-system equation, is related to the variance, and the kinetic orders determine the shape of the distribution. Indeed, the two kinetic orders were used as a shape classi�cation system for continuous as well as discrete distribution functions [731][732][733]. e same distribution was subsequently used in survival analysis and risk assessment [28,625,[734][735][736][737][738], and as a tool for random number generation and quantile analysis [739,740], as well as for inference [741,742].…”
Section: Recastingmentioning
confidence: 99%
See 1 more Smart Citation
“…A few years ago, the S-distribution was introduced as a tool for classifying data and distributions (Voit 1992, Voit andYu, 1994). It has been shown that this distribution is capable of representing various degrees of skewness and that it is structurally rich enough to approximate most densities and mass functions rather well.…”
Section: Introductionmentioning
confidence: 99%
“…Let us mention also the so-called "suprasystem of probability distributions" proposed by Savageau [42] which is a set of simultaneous ordinary differential equations, and the S-system of distributions presented by Voit [53] and defined as a four parameter ordinary differential equations which "appears to be a good candidate for representing and analyzing failure data" ([54, p. 596]). A generalization of the BurrHatke and S-system of distributions has been recently done by the present author and posted on Gnedenko forum [52].…”
Section: Introductionmentioning
confidence: 99%